2017
DOI: 10.1016/bs.ai.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Immunity

Abstract: Organisms throughout biology need to maintain the integrity of their genome. From bacteria to vertebrates, life has established sophisticated mechanisms to detect and eliminate foreign genetic material or to restrict its function and replication. Tremendous progress has been made in the understanding of these mechanisms which keep foreign or unwanted nucleic acids from viruses or phages in check. Mechanisms reach from restriction-modification systems and CRISPR/Cas in bacteria and archaea to RNA interference a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
169
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(182 citation statements)
references
References 259 publications
(260 reference statements)
3
169
0
Order By: Relevance
“…Figure S3A). The particularly strong induction of Tlr7 as sensor (at endosomes or lysosomes) for toxic single-stranded RNA and miRNA (3.5-fold), in comparison to Tlr9 as sensor of single-stranded DNA sequences (2.3-fold) and Tlr3 as sensor of double-stranded RNA (1.3-fold) underlined and elucidated the RNA-toxicity [68, 74, 100] present in the spinal cord tissue of our SCA2 model. It is interesting to note that Ataxin-2 domains were reported to play a role in the miRNA-mediated mRNA degradation [90] and to interact with the microRNA effector DDX6 to mediate quality control of mRNAs [4, 120, 132, 198].…”
Section: Resultsmentioning
confidence: 99%
“…Figure S3A). The particularly strong induction of Tlr7 as sensor (at endosomes or lysosomes) for toxic single-stranded RNA and miRNA (3.5-fold), in comparison to Tlr9 as sensor of single-stranded DNA sequences (2.3-fold) and Tlr3 as sensor of double-stranded RNA (1.3-fold) underlined and elucidated the RNA-toxicity [68, 74, 100] present in the spinal cord tissue of our SCA2 model. It is interesting to note that Ataxin-2 domains were reported to play a role in the miRNA-mediated mRNA degradation [90] and to interact with the microRNA effector DDX6 to mediate quality control of mRNAs [4, 120, 132, 198].…”
Section: Resultsmentioning
confidence: 99%
“…PTI has only recently been discovered to act against viruses in plants ( KĂžrner et al, 2013;Nicaise and Candresse, 2017;Niehl et al, 2016;Yang et al, 2010;Zvereva et al, 2016). RNA-based pathogen-associated molecular patterns (PAMPs) are well-known inducers of immunity in animals (Chow et al, 2018;Hartmann, 2017;Tan et al, 2015;Vabret et al, 2017), and have been shown to induce immunity upon viral and bacterial infection also in plants (Lee et al, 2016;Niehl et al, 2016). The mechanism of dsRNA recognition leading to PTI as well as the mode of action against the infecting virus is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, human TLR9 is predominantly expressed in plasmacytoid dendritic cells and B cells, resulting in a strong type I IFN response via MyD88/IRF7 signaling. Conversely, murine TLR9 is expressed abundantly in myeloid immune cells and can also result in IFN-Îł production and the recruitment of NK, αÎČ-, and γΎ-T cells (Hartmann, 2017; Hornung et al, 2002; Krug et al, 2004; Walker et al, 2010). For example, it has been shown that CMV infection in mice activates a TLR9/MyD88 response that occurs selectively in CD11 + dendritic cells (Krug et al, 2004; Puttur et al, 2016).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%